2016
DOI: 10.1002/jcd.21519
|View full text |Cite
|
Sign up to set email alerts
|

On Skew E–W Matrices

Abstract: An E–W matrix M is a ( − 1, 1)‐matrix of order 4t+2, where t is a positive integer, satisfying that the absolute value of its determinant attains Ehlich–Wojtas' bound. M is said to be of skew type (or simply skew) if M−I is skew‐symmetric where I is the identity matrix. In this paper, we draw a parallel between skew E–W matrices and skew Hadamard matrices concerning a question about the maximal determinant. As a consequence, a problem posted on Cameron's website [7] has been partially solved. Finally, codes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[11] We can always assume without loss of generality that every skew E-W matrix is of the form (4). Examples of skew E-W matrices for small orders have been provided in [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11] We can always assume without loss of generality that every skew E-W matrix is of the form (4). Examples of skew E-W matrices for small orders have been provided in [9].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was proved [9] that skew E-W matrices may only exist when 2n − 3 = α 2 for some integer α (i.e. β = 1), a condition which is believed to be sufficient.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is well known that 2n2 must be a sum of squares . Furthermore, Armario and Frau showed that 2n3 must be a square if X is skew‐symmetric. Indeed, they showed the following:…”
Section: Preliminariesmentioning
confidence: 99%
“…A {1, −1}-matrix B of order n is called an EW matrix if it satisfies (2). Hence, in particular, an EW matrix of order n has determinant…”
Section: Introductionmentioning
confidence: 99%